Analisis Sistem Pembelajaran Online; Persiapan Pra Pembelajaran - Safri, Safri (JSI (Jurnal sistem Informasi) Universitas Suryadarma, 2018)
The development of science and technology makes the distance becomes closer, changes in information systems from offline to online also have an impact on education, His dilemma all the information can be obtained, regardless of valuable science even garbage too also exist. Because everyone can enter information into this virtual world.Teachers/Lecturers/Instructors as a source of knowledge are required to be technologically literate, ready or unprepared they should be able to adapt to online learning because of the times demanding so. In order for learning does not produce the science of teaching abysmal then teachers/lecturers/instructors are required to develop learning instruments before implementing online learning.So like a science then it takes someone to take knowledge from the teacher is to see the morality of the teacher, how to deliver a good, and shorten the way in seeking knowledge even from online learning.